Species-specific expression of major urinary proteins in the house mice (Mus musculus musculus and Mus musculus domesticus) - Stopková, R; Stopka, P; Janotová, K; Jedelský, P L (Journal of chemical ecology, 2007)
The analysis of expression of pheromone-carrying major urinary proteins (MUPs) from two subspecies of house mice (Mus m. musculus, Mus m. domesticus) was studied. It has been previously shown that commensal populations of the two subspecies can discriminate on the basis of urinary signals. MUPs are predominant urinary proteins that protect pheromones from rapid degradation in a hydrophilic environment, and individuals of M. m. musculus tend to rely on these urinary cues in the process of subspecies discrimination more than M. m. domesticus individuals. Although it is not precisely known what triggers phenotypic and epigenetic changes of MUP expression, our results show that in the subspecies M. m. musculus, sex is a significant factor influencing variations in the regulation of selected MUPs in the liver. Furthermore, male M. m. musculus individuals expressed all the studied MUPs' mRNA significantly more than females or individuals of either sex in M. m. domesticus. Correspondingly, the pattern of mRNA abundance was corroborated with the level of total MUP concentration in the urine, such that the level of sexual dimorphism was also significant and species-specific. Our finding introduces a hypothesis that quantitative variation of these proteins may be an essential part of a subspecies recognition system that maintains homospecific mixing.
Keywords: RNA, Messenger; druhová specificita; sekvence nukleotidů; polymerázová řetězová reakce; Male; Sex Characteristics; mužské pohlaví; DNA Primers; pohlavní dimorfismus; elektroforéza v polyakrylamidovém gelu; referenční standardy; Species Specificity; Animals; proteinurie; Electrophoresis, Polyacrylamide Gel; ženské pohlaví; zvířata; myši; DNA primery; Reference Standards; Proteinuria; Polymerase Chain Reaction; Base Sequence; Mice; Female; messenger RNA